Toxoplasma gondii in four captive kangaroos (Macropus spp.) in China: Isolation of a strain of a new genotype from an eastern grey kangaroo (Macropus giganteus). (April 2019) - Su, Ruijing; Dong, Hui; Li, Tongyi; Jiang, Yibao; Yuan, Ziguo; Su, Chunlei; Zhang, Longxian; Yang, Yurong
Abstract: Marsupials are highly susceptible to Toxoplasma gondii infection. Here, we report T. gondii infection in four kangaroos from a zoo in China. Kangaroos were imported into China in 2000 and were since bred in zoo. In 2017–2018, four kangaroos died due to respiratory system disease or injury. The bodies were submitted to the laboratory to test for T. gondii infection. Antibodies to T. gondii were found in 75% (3/4) of the kangaroos via the modified agglutination test with the cut-off 1:25. Cysts were observed in the histopathological sections of tongue and diaphragm or squashes of fresh myocardium in two kangaroos. These cysts were confirmed as T. gondii by immunohistochemical staining and molecular biological analysis. One viable T. gondii strain was isolated from one kangaroo and designated as TgRooCHn1. DNA from T. gondii tachyzoites obtained from cell culture was characterized by 10 PCR-RFLP markers and the virulence genes ROP5 and ROP18. The genotype of this isolate did not match with any known genotypes; it was designated as ToxoDB#292. The virulence of TgRooCHn1 (10 4 tachyzoites) was non-lethal to mice, and it formed tissue cysts. To our knowledge, the present study is the first isolation of ToxoDB#292 strain from kangaroo. Improvemets for captive settings were initiated, including greater attention being paied to birds and stray cats, fed frozen meat for carnivores. Graphical abstract: Image 1 Highlights: T. gondii infection in kangaroo was confirmed by serological and molecular analysis, histopathology, and bioassay in mice. One viable T. gondii strain (ToxoDB#292) was isolated from one kangaroo. The virulence of TgRooCHn1 in mice was low and it formed tissue cysts.